2017
DOI: 10.1186/s40529-017-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fungal activity, mechanism studies on α-Phellandrene and Nonanal against Penicillium cyclopium

Abstract: BackgroundEssential oils from plants have been reported to have wide spread antimicrobial activity against various bacterial and fungal pathogens, and these include α-Phellandrene, Nonanal and other volatile substances. However, biological activities of α-Phellandrene and Nonanal have been reported only in a few publications. Further investigations are necessary to determine the antimicrobial activity of these compounds, especially for individual application, to establish the possible mechanism of action of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 38 publications
(50 reference statements)
4
58
0
Order By: Relevance
“…Besides, nonanal appeared in the first two weeks and was a substance with aroma, the highest content of which was 4.12%. This is a substance widely found in tea, tobacco, roses, etc., with a strong odor and safe edible properties . Ester compounds were the most abundant substances, a total of nine species, the lowest ester content on the fifth day, the most on the fourteenth day, and the most content was lambertionsaeure‐methyl ester accounting for 15.27%, ester compounds had a special aroma, they may be the source of the fragrance, while accounting for the second most in the total composition, second only to acids.…”
Section: Resultsmentioning
confidence: 98%
“…Besides, nonanal appeared in the first two weeks and was a substance with aroma, the highest content of which was 4.12%. This is a substance widely found in tea, tobacco, roses, etc., with a strong odor and safe edible properties . Ester compounds were the most abundant substances, a total of nine species, the lowest ester content on the fifth day, the most on the fourteenth day, and the most content was lambertionsaeure‐methyl ester accounting for 15.27%, ester compounds had a special aroma, they may be the source of the fragrance, while accounting for the second most in the total composition, second only to acids.…”
Section: Resultsmentioning
confidence: 98%
“…The B. spectabilis extract was more effective than C. spinosum extract, and this may be because it contains aldehydes and huge amounts of volatile compounds, such as nonanal, which was found in the phytochemical analysis at a percentage of 38.28%. The biological activities of nonanal have only been reported in a few publications, as it significantly inhibits the mycelia growth of P. cyclopium [76].…”
Section: Discussionmentioning
confidence: 99%
“…There are previous reports that straight-chain alcohols (Weber and de Bont, 1996), weak organic acids (Ullah et al, 2012), and nonanal (Zhang et al, 2017) all increase membrane permeability, and there is considerable overlap between the downstream effects of membrane permeabilization and the effects that we observed. Cells can repair their membranes from permeabilizers within minutes (Idone et al, 2008) or even seconds (McNeil et al, 2000), and the efficacy of this process is proportional to the concentration of the permeabilizer (Idone et al, 2008).…”
Section: Discussionsupporting
confidence: 60%
“…Fernando et al, 2005;Kobaisy et al, 2001;Rajer et al, 2017), its mechanism of action has not been wellstudied. To the best of our knowledge, there is only one report on its antifungal mode, which showed that nonanal decreased membrane stability and increased membrane permeability in Penicillium cyclopium (Zhang et al, 2017).…”
Section: Figure 21 Structures Of the Four Volatile Compounds Examinmentioning
confidence: 99%